Numerical study on dynamic response of hollow and cavity type clay brick masonry infill panels subjected to blast loading. (April 2023) - Shamim, Saba; Ahmad, Shakeel; Khan, Rehan A.
Highlights: Experimental exploration of material properties of Hollow and Cavity brick masonry prisms. Validation of Non-linear Single degree of Freedom (SDOF) and Finite Element (FE) models of Hollow and Cavity brick masonry walls subjected to blast. Investigation on the effect of nature of explosion and height of detonation on both types of masonry walls. Investigation on effectiveness of suggested low cost strengthening technique for Hollow brick masonry wall against blast load. Abstract: Laboratory and prototype study of masonry panel subjected to earthquake, wind and impact is relatively easy however, the experimental study of masonry panel under the action of blast phenomenon is quite a risky and restrictive work area to perform. But computational advancement has made it within our capabilities and is deemed to yield acceptable results. Therefore, this study focuses on investigating the dynamic blast response of novel hollow and cavity type clay brick masonry (HBM and CBM) infill panels enclosed in reinforced concrete (RC) frames using explicit finite element (FE) method. The properties of HBM and CBM required for defining the numerical FE model were derived from the experimental tests. Moreover, due to lack of experimental study on HBM and CBM subjected to the action of blast, the FE peak displacement observed at mid-height of masonry panels were agreeably validated with the peak displacement obtained from an equivalent non-linear single degree of freedom (SDOF) model wherein, a link between positive phase duration of blast and natural time-period of structure is established. Further, the effects of nature of explosion, standoff distance, weight of explosive and height of detonation from ground level were investigated for HBM and CBM walls. Thereafter, HBM panel was strengthened using a low-cost technique, making use of steel bars for enhancing the out-of-plane stiffness of the wall against blast loading. Reinforced hollow brick masonry (RHBM) panel was found to be an excellent alternative for blast load mitigation.